Exploring Paddy Profitability Trends: A Comparative Analysis Across Five Major Growing States of India - Chanakya, M.; Nandi, A. K. (International Journal of Economic Plants, 2024)
This research delves into the dynamics between the market value of the product of paddy and the associated costs of its cultivation across prominent paddy producing regions in India. Drawing upon secondary data from the period 2004–05 to 2021–22, generously provided by the Commission for Agricultural Costs and Prices (CACP), this study employs growth models and profitability analyses to shed light on emerging patterns within these key states. A detailed examination reveals Punjab as leading in terms of value growth, closely followed by Andhra Pradesh and West Bengal. In contrast, the escalation in cultivation costs is most pronounced in Andhra Pradesh, with Punjab, West Bengal, and Uttar Pradesh also showing significant figures. Through an insightful profitability assessment, the study demonstrates that paddy cultivation is most lucrative in Punjab, with Andhra Pradesh, Uttar Pradesh, and West Bengal following in descending order of profit margins. This hierarchy of profitability signals an imperative for regions like West Bengal and Uttar Pradesh to elevate the quality and market value of their paddy crops to match the standards seen in Punjab and Andhra Pradesh. The comparative advantage enjoyed by farmers in Punjab and Andhra Pradesh in terms of profit margins underscores the critical importance of enhancing productivity, efficiency, and market connectivity in the lesser-performing states of West Bengal and Uttar Pradesh. Such improvements are essential for boosting profitability in paddy cultivation, thereby contributing to the overall growth and sustainability of the agricultural sector in these regions.